Are you (not) expecting? The unforeseen benefits of job training on teenage pregnancy - Rafael Novella; Laura Ripani (IZA Journal of Labor & Development, 2016)
Teenage pregnancy in the Dominican Republic represents a persistent development challenge. This paper uses data from a randomized impact evaluation of the youth training program Juventud y Empleo, which includes soft skills training, to examine its impact on teenage pregnancy. We find that the program reduces the probability of teenage pregnancy by 8 percentage points (about 20 %), particularly among teenagers who are not already mothers. The program seems to affect teenage pregnancy through improvements in soft skills and expectations, among other channels. In addition, we find that the program plays a protective role for teenagers from more deprived backgrounds.
Keywords: J24; J13; O15; 330; Teenage pregnancy; Youth training programs; Soft skills; Dominican Republic